Adenosine Triphosphate, Polymyxin B and b16 Cell-Derived Immunization Induce Anticancer Response - Imarai-Bahamonde, C; Acuna-Castillo, C; Milla-Brito, L; Leiva-Salcedo, D; Robles-Planells, C; Rojo-Castillo, L; Mena-Silva, J; Barrera-Ávalos, C (Future Medicine Ltd., 2021)
Aim: Whole dead tumor cells can be used as antigen source and the induction of protective immune response could be enhanced by damage-associated molecular patterns. Materials & methods: We generated whole dead tumor cells called B16-immunogenic cell bodies (ICBs) from B16 melanoma cells by nutrient starvation and evaluated the in vivo antitumor effect of B16-ICBs plus ATP and polymyxin B (PMB). Results: The subcutaneous immunization with B16-ICBs + PMB + ATP a 50% of tumor-free animals and induced a significant delay in tumor growth in a prophylactic approach. These results correlated with maturation of bone marrow-derived dendritic cells and activation of T CD8+ lymphocytes in vitro. Conclusion: Altogether, ICB + ATP + PMB is efficient in inducing the antitumor efficacy of the whole dead tumor cells vaccine. © 2021 Future Medicine Ltd.. All rights reserved.